The consequences of introducing IT systems for decision-making processes in healthcare institutions - Marzena Furtak-Niczyporuk; Marek Kos; Michał Albiniak; Anna Jurek (Kazimierz Wielki University, 2017)
Introduction: The measures currently being implemented in the field of healthcare systems are being directed towards minimising the costs incurred by healthcare institutions, while improving the quality of health services provided to patients. It seems essential to make use of various types of instruments supporting the process of making rational management decisions. IT systems constitute an effective tool, creating databases which are significant in supporting management functions in healthcare institutions. In particular, these tools, due to their automatic search and synthesis of information, play a major role in making rational management decisions in the shortest possible time.       Aim: The aim of the study was the diagnosis of management decision-making in the therapeutic entity, for possible implementation tools in the form of an information system, which could accelerate and support the rational process of making those decisions. In addition, work was to evaluate the role of management decisions and the implications of the information system on the process of rational decision-making in the management entity therapeutic.   Material and Methods: The case study method allowed us to show the practical applications and benefits resulting from the application system to support rational decision-making management, in particular in terms of reducing costs and improving the organization of health services offered.   The results and conclusions: Presented system generates a database to support rational decision-making process in the field of management, minimize their costs while improving the organization of health services. Ability to use various functions of the system allows for multi-segment analysis, thanks to the specially chosen and condensed information, both in the form of text and graphics over any time horizon. Benefits of the implications of the system is the speed and efficiency of the whole process of treatment, as well as the reduction of administrative tasks of medical staff, which increases the time for the patient.